No association between cardiometabolic risk and neural reactivity to acute psychosocial stress - Lederbogen, Florian; Streit, Fabian; Deuschle, Michael; Tost, Heike; Meyer-Lindenberg, Andreas (NeuroImage: Clinical, 2018)
Background - Exaggerated reactivity to acute psychosocial stress is associated with an increased risk of cardiovascular and metabolic disease. A dysfunction of the cortico-limbic network coordinating the peripheral adaptation to acute stress exposure may constitute a brain mechanism underlying this association. We opted to characterize the changes of this network associated with acute psychosocial stress exposure in individuals with low and high cardiometabolic risk (CMR). - Methods - In 57 subjects without overt cardiac or cerebral disease, the Framingham risk score and presence/absence of type 2 diabetes or metabolic syndrome defined CMR. Psychosocial stress was induced during functional magnetic resonance imaging (fMRI) of brain activity by an established social threat paradigm. Measurements of heart rate, blood pressure and saliva cortisol quantified the peripheral stress reaction. Regression analyses for the anterior cingulate cortex, hippocampus, amygdala, insula and regulatory prefrontal regions evaluated the association of stress-associated brain activation and CMR. - Results - Psychosocial stress exposure was associated with an increased activity of a brain network including anterior and posterior cingulate cortex, putamen, insula, parahippocampus and right hippocampus. Psychosocial stress-associated brain activation did neither covary with Framingham risk score nor differ between groups with low or high CMR. - Conclusion - Exposure to acute psychosocial stress induces the activation of a well-defined cortico-limbic network. However, we did not find an association between CMR and this network's stress reactivity.
Gesehen am 25.02.2020